Types de dominance agressive dans une colonie constituée exclusivement de males chimpanzés : intensité, fréquence, durée et direction de l'agression - Nerea Amezcua Valmala; Javier de Echegaray y Díaz de Otazu; Belén Fernández Castilla; Catarina Casanova; Fernando Colmenares (Revue de Primatologie)
Living in groups entails several fitness benefits but also leads to conflicts of interest. The strategies that different species have evolved to manage these conflicts are diverse and in some species aggressive exchanges of various kinds are commonplace. In some species, aggressions are important contributing elements to the organization of their social systems, providing a social order that may serve to avoid future agonistic encounters. Male chimpanzees are known for being gregarious, for exchanging complex social interactions and for forming dominance relationships where aggressions of different intensities can be frequent. Aggressions are costly interactions as they are energetically demanding but also because they encompass social consequences and risks. In this study we aimed to investigate the relationship between aggressive dominance styles and the intensity, the frequency, the duration and the direction of the aggressive interactions in a group of ten young male chimpanzees (“Pan troglodytes verus”) housed at la Vallée des Singes in France. First, we investigated whether aggressive interactions were costly behaviors; for this, we classified aggressions into three intensity levels, low, middle and high; we expected to find that if they were energetically demanding, then a negative relation between intensity and duration of aggressive interactions should be obtained. Second, we investigated whether the rank order of individuals varied depending on whether we assessed occurrence of aggression or duration of aggressive episodes for each one of the three levels and for the pooled category. Next, we correlated the two rank orders thus obtained. Finally, we studied whether aggressive dominance rank orders were consistent across the various aggression-based measures. As expected, we found that low intensity aggressions lasted longer than did medium and high aggressive exchanges. With both measures, occurrence and duration, we found similar aggressive patterns for the three levels of aggressions and for the totality of aggressive behaviors. Finally, we found some minor but interesting differences in the aggression-based dominance rankings when we compared individual measures, dyadic measures, the h’ de Vries dominance index and the David’s Score method. Our results suggest that due to the consistency of several measures, aggressive interactions are valuable to study aggression dominance in this species and that these interactions are selectively used. We also believe that although probing into the aggressive dominance relationships of male chimpanzees can provide a more nuanced view of their social relationships, a fuller understanding of this species’ group structure and dominance hierarchies should also incorporate other agonistic behavioral interactions (e.g., submission) and affiliative measures. Partly funded by project grant SFRH/BD/69069/2010 to NAV and PSI2011-29016-C02-01 to FC.